Abnormal attentional modulation of retinotopic cortex in parietal patients with spatial neglect. - Vuilleumier, P; Schwartz, S; Verdon, V; Maravita, A; Hutton, C; Husain, M; Driver, J (2008)
Brain regions beyond visual cortex are thought to be responsible for attention-related modulation of visual processing [1, 2], but most evidence is indirect. Here, we applied functional magnetic resonance imaging (fMRI), including retinotopic mapping of visual areas, to patients with focal right-parietal lesions and left spatial neglect [3, 4]. When attentional load at fixation was minimal, retinotopic areas in right visual cortex showed preserved responses to task-irrelevant checkerboards in the contralateral left hemifield, analogously to left visual cortex for right-hemifield checkerboards, indicating a "symmetric" pattern in both hemispheres with respect to contralateral stimulation under these conditions. But when attentional load at fixation was increased, a functional asymmetry emerged for visual cortex, with contralateral responses in right visual areas being pathologically reduced (even eliminated for right V4/TEO), whereas left visual areas showed no such reduction in their contralateral response. These results reveal attention-dependent abnormalities in visual cortex after lesions in distant (parietal) regions. This may explain otherwise puzzling aspects of neglect [5, 6], as confirmed here by additional behavioral testing.